Determination of molecular hydration in solution via changes in magnetic anisotropy. Issue 30 (28th March 2023) - Giansiracusa, Marcus J.; Vonci, Michele; Whyatt, Yasmin L.; Williams, Carys; Mason, Kevin; Parker, David; McInnes, Eric J. L.; Chilton, Nicholas F.
Abstract : The hydration behaviour of coordination complexes is important for understanding their roles as bio-imaging agents. We use EPR to determine that a carboxylate PARASHIFT reagent coordinates water while the phosphinate analogue does not. Abstract : The hydration behaviour of coordination complexes is important for understanding their roles as bio-imaging agents. Determination of hydration is difficult, and various optical and NMR-based techniques have been used. Here we use EPR spectroscopy to unambiguously demonstrate that a t -butyl-pyridyl-functionalised Er III DOTA derivative coordinates water, while its methylphosphinate analogue does not.